Analisis Pengaruh Penggunaan Fin Terhadap Peningkatan Perpindahan Kalor Pada Alat Penukaran Kalor Untuk Menyimpan Kalor Laten - Erizal Erizal (UNIVERSITAS PROF. DR. HAZAIRIN, SH BENGKULU, 2019)
Abstrack The fin effect on heat transfer rate of a heat exchanger for laten thermal energy strorage system using the latent heat of fusion of a phase change material (PCM) has been studied. The head storage container consist of a double pipe heat exchanger, where the energy source (hot water) flows through the copper inner finned tube of 12,5 mm inside diameter with 1,75 mm thick and 1495 mm length, while the heat sink (storage PCM) fills the annulus gap (outer pipe consists of PVC of 78 mm inside diameter with thicknessof 6 mm) The PCM used in the experiments is paraffin wax of melting temperatur 44? C. Heat transfer rate and accumulated energy stored into PCM as a function of taim were determined for differentwater flow rates and water inlettemperatures.The experimental results have been compared to the one obtainedby the plaintu tube heat exchanger. The results show that substituting a seriesof fin on the surface of inner tube of heat exchanger significantly increases the heat transfer rate and accumulated energy in the system.